Connecting Historic Perservationists: A Proposed Partnership Based on the ERIC Model - Henderson, Martha V.; Jarred, Ada D. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Studies reveal that information needs of historic preservationists are unmet by current resources. This paper analyzes the Educational Resources Information Center system and parallels the need for analogous services to the field of historic preservation. Emerging technologies enable partnerships connecting information, entities, and individuals in all preservation disciplines.